2022
DOI: 10.3390/en15238952
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study for Enhancement of Heat Transfer Using Discrete Metal Foam with Varying Thickness and Porosity in Solar Air Heater by LTNE Method

Abstract: A two-dimensional rectangular domain is considered with a discrete arrangement at equal distances from copper metal foam in a solar air heater (SAH). The local thermal non-equilibrium model is used for the analysis of heat transfer in a single-pass rectangular channel of SAH for different mass flow rates ranging from 0.03 to 0.05 kg/s at 850 W/m2 heat flux. Three different pores per inch (PPI) and porosities of copper metal foam with three different discrete thicknesses at equal distances are studied numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The impact of various factors on the convection-radiation heat transfer and flow structures within a solar heater Adopting porous substrate into SAH significantly increases the Nusselt number (Nu) [26] Brinkman-Forchheimer extended Darcy model The heat transfer equation has been solved analytically based on the perturbation method Temperature-dependent radiative conductivity was used to evaluate the performance of a porous channel solar collector Radiation has a more significant impact on collector thermal performance and the Nu than the porous shape parameter [31] Brinkman-Forchheimer extended the Darcy model with the LTE model The influence of porous blocks' height, number, permeability, and arrangement were studied For the porous channel, it is confirmed that the extended Darcy-Brinkman-Forchheimer model is the right choice Optimal performance is attained when the inlet and outflow are free of porous blocks [33] Brinkman-Forchheimer extended the Darcy model with the LTE model The thermal characteristics of conjugated porous blocks within FPSC were investigated The highest performance is observed when the height of the block is lower near the inlet and higher near the outflow [34] Darcy -extended Forchheimer model, with LTNE model Utilization of discrete metal foam blocks with varying thickness and porosity in SAH Employing a discrete arrangement of metal foam reduces pressure drop while maintaining effective heat transmission [35] Brinkman-Forchheimer extended the Darcy model with the LTE model Present an innovative design for enhancing the thermal performance of a flat-plate solar collector (FPSC) via porous media…”
Section: Problem Description and Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of various factors on the convection-radiation heat transfer and flow structures within a solar heater Adopting porous substrate into SAH significantly increases the Nusselt number (Nu) [26] Brinkman-Forchheimer extended Darcy model The heat transfer equation has been solved analytically based on the perturbation method Temperature-dependent radiative conductivity was used to evaluate the performance of a porous channel solar collector Radiation has a more significant impact on collector thermal performance and the Nu than the porous shape parameter [31] Brinkman-Forchheimer extended the Darcy model with the LTE model The influence of porous blocks' height, number, permeability, and arrangement were studied For the porous channel, it is confirmed that the extended Darcy-Brinkman-Forchheimer model is the right choice Optimal performance is attained when the inlet and outflow are free of porous blocks [33] Brinkman-Forchheimer extended the Darcy model with the LTE model The thermal characteristics of conjugated porous blocks within FPSC were investigated The highest performance is observed when the height of the block is lower near the inlet and higher near the outflow [34] Darcy -extended Forchheimer model, with LTNE model Utilization of discrete metal foam blocks with varying thickness and porosity in SAH Employing a discrete arrangement of metal foam reduces pressure drop while maintaining effective heat transmission [35] Brinkman-Forchheimer extended the Darcy model with the LTE model Present an innovative design for enhancing the thermal performance of a flat-plate solar collector (FPSC) via porous media…”
Section: Problem Description and Assumptionsmentioning
confidence: 99%
“…Keeping the block's height low near the inlet and high near the outflow produced the best performance factor of 2.163. A numerical investigation was carried out by Diganjit et al [35] to improve heat transmission by utilizing discrete metal foam blocks with varying thickness and porosity in SAH. The Nu improved by 157.64% to 218.60% compared to the empty channel.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the change in density due to fluid velocity is less than 5%. Hence, the flow is assumed to be incompressible [1,40,48,49]. The experimental parameter assumed for global radiation incident on the SAH, ambient temperature, fluid flow rate, temperature rise across SAH, and fluid inlet temperature are assumed to be within ±50 W/m 2 , ±1 • C, ±1%, ±1 • C, and ±1 • C, respectively, within a 15 min duration [1].…”
Section: Governing Equationsmentioning
confidence: 99%
“…SAHs have generally low efficiency, so instead of increasing the number of SAHs to meet the energy demand, the main purpose of this study is to increase the efficiency of SAHs. Various kinds of turbulators that are in use are pin fin arrays, [ 1 ] dimples, [ 2 ] rib, [ 3,4 ] matrix, [ 5 ] wire mesh, [ 6 ] and corrugation. [ 7 ] Turbulators are formed in the way of fluid flow to increase turbulence in the channel.…”
Section: Introductionmentioning
confidence: 99%